VALIDITY OF GUIDED INQUIRY-BASED LEARNING INSTRUMENT WITH GEOGEBRA APPLETS FOR TEACHING CIRCLES - Stri Pertiwi; Mailizar Mailizar; Elizar Elizar (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The guided inquiry learning model is a student activity that emphasizes maximally training critical thinking skills. The learning instruments developed must be adapted to the syntax/stages of the guided inquiry learning model. Several learning instruments have been developed to assist teachers in making teaching materials. However, many teachers have not mastered technology, especially learning media using applications. Therefore, teachers need learning applications in schools, such as the GeoGebra applet. This study aims to develop valid guided inquiry-based learning instruments using GeoGebra applets for circles. This research is development research employing Plomp’s model and involving preliminary research and prototyping stages. The data was collected by compiling the comments and input from the validator through validation sheets related to learning instruments (lesson plans, worksheets, and GeoGebra applets). The results of the data analysis showed that the learning instruments were declared valid with an average lesson plan score of 4.75, an average student worksheet validation score of 4.60, and an average value of the total validation of GeoGebra applets of 4.94. Further research should assess the practicality and effectiveness of the instruments.